Iatrogenic Pulmonary Nodule in a Heart Transplant Recipient - Atul C. Mehta; Juan Wang; Jarmanjeet Singh; Joseph Cicenia (Case Reports in Pulmonology)
A 58-year-old female with a history of non-Hodgkin lymphoma and end-stage nonischemic cardiomyopathy from Adriamycin toxicity underwent orthotic heart transplantation during June 2013. She developed shortness of breath in September 2013 and was suspected to have invasive pulmonary aspergillosis. A flexible bronchoscopy (FB) with a transbronchial biopsy (TBBx) was performed. She was found to have a focal lung nodule in the same location at the site of the TBBx on day 13 after the FB. Spontaneous resolution of the nodule was confirmed on the computed tomography (CT) scan of chest performed at 3 months. We believe that this nodule was as a consequence of the TBBx. Formation of a peripheral pulmonary nodule (PPN) following a TBBx is occasionally encountered among the recipients of the lung transplantation. To our knowledge, this is the first case of TBBx producing a pulmonary nodule in a heart transplant recipient. Physicians caring for the patients with heart transplantation should be cognizant of the iatrogenic nature of such nodule to avoid unnecessary diagnostic work-up.